Designing a Digital Research Accelerator Programme for the Social Sciences at UCD: Preliminary Results of a Faculty-Library Collaboration. Issue 2 (1st October 2020) - Fulton, Crystal; Bustillo, Marta; McGuinness, Claire; Guerin, Suzanne; Browne, Andrew
Abstract: Alongside calls in the literature for research skills development for undergraduates, University College Dublin's College of Social Sciences and Law (CoSSL) has identified a need for research skills education for its new Bachelor of Social Sciences programme. In collaboration, academics and the library have created a new course, the Social Sciences Research Accelerator, designed to provide foundational learning of research skills for students transitioning to conduct research projects in their final year. Preliminary testing of the course, which included a small user-testing group of undergraduates who engaged with course activities and then completed a survey evaluation, has been positive. This paper details the partnership between academics and library staff towards a common scholarship goal, including the creation of learning materials, early testing of content, and future work.